Machine Learning Algorithms for Biomedical Image Analysis and Their Applications - Francesco Prinzi; Ines Prata Machado; Carmelo Militello (Algorithms, 2025)
In recent years, architectural and algorithmic innovations in machine learning have revolutionized the analysis of medical images [...]